PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN ( Studi Pada Konsumen Rumah Makan Padang “Surya” Semarang ) - Arisqi Dwi Hendarto, 12.05.51.0160 (Students' Journal of Economic and Management, 2016)
The objectives of this study is to analyze the impact of the service quality, price perception and location on purchasing decission at Padang Restaurant “Surya” in Semarang. The sample which used by this is about 100 respondents with sampling technique by using Accidental Sample method. The data which is used is premiere data, the analytical data which is used involving validity test, reliability test, multiple regression linear test, coefficient of determination and hypothesis test involving F test and t test. Based on the data analysis and hypothesis test showed that partially, the service quality variable is positively and significantly affected on the purchasing decisions. Price perception variable is positively and significantly affected on the purchasing decisions. Location variable is positively and significantly affected on the purchasing decisions.